2016
DOI: 10.3892/ol.2016.4714
|View full text |Cite
|
Sign up to set email alerts
|

In vitro generation of cytotoxic T lymphocyte response using dendritic cell immunotherapy in osteosarcoma

Abstract: Abstract.Immunotherapy with tumor lysate-pulsed dendritic cells (DCs) is one of the breakthrough strategies used in the treatment of cancer. However, DC-based immunotherapies for osteosarcoma are limited. In the present study, preclinical studies of a C3H osteosarcoma mouse model (produced by subcutaneous injection of LM8 murine osteosarcoma cells) validated the concept that LM8 cell lysate-pulsed bone marrow-derived DCs may evoke a more potent immune response compared with DCs that have been matured using pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Masanori Kawano et al [27] reported that combining agonist antiglucocorticoid-induced tumor necrosis factor receptor (GITR) antibodies with tumor lysate-pulsed dendritic cells reduces the amounts of immunosuppressive cytokines in OS tissues as well as serum. Furthermore, it has been confirmed that pulsing of dendritic cells with LM8 cell lysate, derived from OS, efficiently enhances CD4 + and CD8 + T cell proliferation and decreases serum interleukin-4 [28]. While assessing synergistic effects with chemotherapy, it was found that combining doxorubicin, which induces immunogenic cell death, with resting dendritic cells boosts systemic immune reactions, leading to OS inhibition in mouse models [29].…”
Section: Discussionmentioning
confidence: 93%
“…Masanori Kawano et al [27] reported that combining agonist antiglucocorticoid-induced tumor necrosis factor receptor (GITR) antibodies with tumor lysate-pulsed dendritic cells reduces the amounts of immunosuppressive cytokines in OS tissues as well as serum. Furthermore, it has been confirmed that pulsing of dendritic cells with LM8 cell lysate, derived from OS, efficiently enhances CD4 + and CD8 + T cell proliferation and decreases serum interleukin-4 [28]. While assessing synergistic effects with chemotherapy, it was found that combining doxorubicin, which induces immunogenic cell death, with resting dendritic cells boosts systemic immune reactions, leading to OS inhibition in mouse models [29].…”
Section: Discussionmentioning
confidence: 93%
“…Numerous immunotherapies were assessed to modulate the tumor microenvironment and to reactivate a prolonged and efficient immune response [6]. Adoptive cell therapies based on TIL as described above and generating antigen-specific lymphocytes [103][104][105], dendritic cells [106][107][108][109][110][111][112], NK cells [113][114][115][116][117][118] were developed mostly in vitro and in pre-clinical model of osteosarcoma. Several clinical trials are currently in progress for evaluating their therapeutic efficacy in patients (Table 1).…”
Section: Lymphocytes Subpopulations In Osteosarcoma and Therapeutic Imentioning
confidence: 99%
“…Recently, various kinds of cellular immunotherapy for advanced sarcomas have been developed [38]. Treatment of DCs pulsed with tumor lysate significantly increased induction of cytotoxic T lymphocyte (CTL) activity and increased the serum level IFN- γ [39]. DCs have been used to enhance tumor-specific immune responses because DCs are major antigen-presenting cells initiating cellular immune responses in vivo [40].…”
Section: Role Of the Immune System And Advancement In Immunotherapmentioning
confidence: 99%